SMOKING POLICIES IN FEDERAL BUILDINGS: A SURVEY BY THE OFFICE OF U.S. SENATOR FRANK R. LAUTENBERG (D-NJ) (Tufts Archival Research Center, 2007)
Press release from Frank Lautenberg, a U.S. Senator (D-NJ). Presents results of a survey on smoking policy in federal buildings. Outlines the smoking restrictions (or lack thereof) in place in various legislative offices, executive departments, independent government agencies and judicial offices.